A6 NC mmd by GPC and CHN at AWE N Barnett.pdf - Gill, Philip (Cranfield University, 2023)
Progress toward reliable NC molecular mass distribution by GPC, plus a small introduction to CHN Nicola Barnett - AWE
Keywords: 'nitrocellulose'